Past and present biodiversity in northeastern Siberia inferred from sedimentary DNA metabarcoding - Huang, Sichao (2021)
The arctic-boreal treeline is a transition zone from taiga to tundra covering a vast area in Siberia. It often features large environmental gradients and reacts sensitively to changes in the environment. For example, the expansion of shrubs and a northward movement of the treeline are observable in Siberia as a response to the warming climate. The changes in vegetation across the treeline are known to influence the water chemistry in the lakes. This causes further alteration to the composition and diversity of sensitive aquatic organisms such as diatoms and macrophytes. Despite the rising awareness of the complex climate-feedback mechanisms of terrestrial plants, the understanding of their assembly rules and about responses of aquatic biomes in the surrounding treeline lakes is still limited. The goal of this thesis is to examine the previous and present biodiversity of terrestrial and freshwater biomes from the Siberian treeline ecotone, as well as their reactions to environmental changes. In particular, this thesis attempts to examine the performance of applying sedimentary DNA metabarcoding in terrestrial plants, aquatic macrophytes and diatoms, their spatial patterns along the environmental gradients and their temporal patterns throughout the climate transition from the late Pleistocene to Holocene. Sedimentary DNA metabarcoding combined with next-generation sequencing is applied as a primary tool to explore the composition and diversity of terrestrial plants, diatoms and aquatic macrophytes. The main study area is located in Chukotka of northeastern Siberia in the Arctic, a biodiversity hotspot due to its continental location and the diverse habitats of the glacial refugium. The modern diatom diversity was assessed with a specific diatom metabarcoding marker and morphological identification. Both approaches agree to a dominance of Fragilariaceae and Aulacoseiraceae, as well as on the environmental influential indicators of the diatom community. The high diversity of Fragilariaceae identified in the ...